The Effect of The Role Playing Model Assistant Skepita Media (Story Interaction Schemes) on The Ability to Reset The Story Content - Hanna Putri Ramadhani; Tria Mardiana; Puji Rahmawati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to determine the effect of Role Playing assisted by Skepita media on the ability to retell the story content of fourth grade students at SD Negeri Trasan 2, Bandongan District, Magelang Regency. This study uses a Pre-Experimental Design research type with the One Group Pre-test Post-test Design model. Research subjects were selected by non-probability sampling saturated sampling model. Samples were taken as many as 25 students. by using data collection methods in the form of description tests and observations. The validity test for the critical thinking ability description test uses the Pearson formula. The reliability test used cornbach's alpha with the help of IBM SPSS 25. In addition, the researcher used a difficulty level test and a discriminatory power test. Data analysis used a non-parametric statistical technique, namely the Wilcoxon test. The results showed that the calculation of the average score of the posttest description test was 85.00 which was greater than the test results in the pre-test with an average value of 56.80. The calculation of the observation assessment in the pretest activity was 45.2 and the post-test was 85.50 in the post-test activity. This is evidenced by the results of the Wilcoxon test analysis which shows that Zcount is -4.375 with a significance value of 0.00 <0.05, meaning that there is a significant difference between the results of the pre-test and post-test using the Role Playing Model assisted by Skepita media. The results of this study can be concluded that the use of role playing model assisted by skepticism media has a significant effect on the ability to retell story content.